Groundwater Quality Appraisal of Some Hand-Dug Wells and Boreholes around Okemesi and Ikoro Area, Southwestern Nigeria (Global Journal of Science Frontier Research, 2012)
The study area falls within the basement complex of southwestern Nigeria. The dominant lihologic units are quartzites of Effon Psammite Formation which occur mostly as massive quartzites, schistose quartzites and quartzite schists. Fifteen (15) water samples were collected from the study area at regular intervals which includes nine (9) samples from Okemesi Ekiti and six (6) samples from Ikoro Ekiti respectively. These samples were analysed in order to determine their physical, chemical and bacteriological characteristics. The physiochemical results showed that temperature ranges between 26.7ÂºC-27.7ÂºC, conductivity (80-1680)Î¼s/cm, appearance is clear, colour in hazen scale is
Keywords: Okemesi; Ikoro; Lithologies; Parameters; Statistics